2016
DOI: 10.21101/cejph.a4287
|View full text |Cite
|
Sign up to set email alerts
|

Human Papillomavirus Vaccine - Knowledge and Attitudes among Parents of Children Aged 10-14 Years: a Cross-sectional Study, Tîrgu Mureş, Romania

Abstract: SUMMARYAim: Romania ranks first in Europe in terms of mortality from cervical cancer, recording 6.3 times more deaths than the mean in EU countries. Although vaccination campaigns were launched by health officials in Romania, the acceptance rate remained insignificant and programmes were discontinued. A successful vaccination programme requires a high rate of acceptance and accurate information for health professionals and parents. The aim of the study was to evaluate the level of parental knowledge about huma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
27
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 28 publications
3
27
0
1
Order By: Relevance
“…The low HPV uptake rate in both males and females in Hong Kong can be attributed to the attitude and knowledge of parents because it is usually up to parents to decide whether their child is vaccinated [ 24 ] and this decision is often influenced by the knowledge and attitude of parents [ 25 , 26 ]. A multicenter national survey in China reported that only 36.2% of the parents were willing to vaccinate their child [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…The low HPV uptake rate in both males and females in Hong Kong can be attributed to the attitude and knowledge of parents because it is usually up to parents to decide whether their child is vaccinated [ 24 ] and this decision is often influenced by the knowledge and attitude of parents [ 25 , 26 ]. A multicenter national survey in China reported that only 36.2% of the parents were willing to vaccinate their child [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…Notably, the CHIAS harms score was also among the strongest predictors of HPV vaccine initiation after one year among parents of adolescent girls in North Carolina [ 21 ]. Also, fear of side effects was among the main reasons cited for avoiding HPV vaccination (or intent to vaccinate) in cross-sectional studies with Dutch [ 22 ] and Romanian parents [ 23 ]. This suggests that public awareness and patient education interventions should emphasize the HPV vaccine’s post-licensure safety profile [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although vaccination campaigns were launched by health officials in Romania, the acceptance rate remained low and thus the programs were discontinued. A successful vaccination program requires a high rate of acceptance and accurate information for health professionals and parents (2). In 2014, Salavastru et al published an epidemiological study stating that genital infection with HPV has become one of the most frequently viral sexually transmitted diseases.…”
Section: Introductionmentioning
confidence: 99%